Family law and culture in Europe : developments, challenges and opportunities / edited by Katharina Boele-Woelki, Nina Dethloff, Werner Gephart. - Boele-Woelki, Katharina; Dethloff, Nina, 1958-; Gephart, Werner, 1949- (European family law series ;, 2014)
This volume contains the contributions delivered at CEFL's fifth international conference, which focused on comparative and international family law in Europe in their respective cultural contexts. Inter alia this book discusses the new Principles of European Family Law regarding Property Relations between Spouses, the proposed EU private international law regulations for international couples and their property relations, the national laws of a growing number of countries which legislate non-formalised relationships, and the new developments regarding social, biological and legal parentage.